GAMIFICATION IN E-LEARNING: ITS IMPACT ON MOTIVATION AND LEARNING ACHIEVEMENT - Baso Intang Sappaile; Elisa Mayang Sari; Abdun Wijaya (Berajah Journal, 2026)
With e-learning becoming more and more common at all educational levels, the advancement of digital technology has fueled the transformation of the learning process. Low student involvement and motivation, however, continue to be obstacles to the adoption of online learning. Gamification, or the use of game elements in an educational setting to improve learning, is one popular strategy to deal with this problem. The purpose of this study is to examine how gamification in e-learning affects learning outcomes and student motivation. A literature study was the research methodology employed, looking at numerous pertinent books, scholarly publications, and scientific papers about gamification in digital learning environments. According to the study's findings, gamification components including points, badges, levels, challenges, leaderboards, and reward systems can boost students' motivation both internally and externally. Additionally, by making learning more engaging and pleasurable, gamification enhances academic accomplishment, learning persistence, active involvement, and engagement. However, the learning design, student characteristics, and how well the game components fit the intended learning objectives all affect how effective gamification is. In order to maximize the advantages of e-learning-based learning processes, gamification must be implemented in a methodical manner. This study advances a more comprehensive knowledge of gamification's function as a cutting-edge tactic to raise the caliber of online education in the age of educational reform.